الكتابة للصورة التلفزيونية في الأفلام التسجيلية الوثائقية - شرف, صالح يوسف (Gezira Journal of Educational Sciences and Humanities; مجلد 17 عدد 2 (2020), 2021)
هدف هذا البحث إلى التعرف على متطلبات الكتابة للصورة التلفزيونية في الأفلام التسجيلية الوثائقية، استخدم الباحث المنهج الوصفي التحليلي وطريقة تحليل المضمون، وتم اختيار العينة العشوائية البسيطة لعدد(11) حلقة من جملة (75) تم إنتاجها من سلسلة "زول سوداني" التلفزيونية بين عامي 2016-2019م. كما هدف البحث إلى الوقوف على قواعد الكتابة للصورة في الأفلام التسجيلية وأيضاً التعرف على تجربة إنتاج الأفلام التسجيلية الوثائقية في الفضاء السوداني، كما حاول الإجابة عن جملة من التساؤلات من بينها: ما الاشتراطات المطلوبة للكتابة للصورة التلفزيونية ؟ وما الأشكال الفنية التي يتم تضمينها سلسلة"زول سوداني"التسجيلية؟ وتوصل البحث إلى العديد من النتائج أهمها: الأسلوب التقريري المباشر شكل عنصر ضعف في كتابة الحلقات لاعتماده على شرح ما تُظهره الصورة دون ميل إلى التحليل بغية الوصول بالمشاهد إلى رؤية أكثر إقناعاً وتصديقاً ومن ثَم تشجيعاً على احتذاء المَثل، واعتماد خط نجاح الشخصية المعروضة. واعتماد صناع العمل لمبدأ (5 ثوان فأقل) في الانتقال بين اللقطات وعدم اللجوء إلى تكرار المشاهد إلا عند الضرورة رفع من قيمة العمل المقدم وأبعده عن التقليدية والملل. أوصى البحث بِحَثِّ منظمات المجتمع المدني لإنتاج برامج توثيقية ورعايتها بحيث تعمل على ترسيخ الصورة الذهنية الإيجابية عن الشخصية السودانية والسودان كله مع تَوافر الشواهد وتَعدد القصص والتجارب، ورفع درجة الاهتمام بالمنتج الفني الوثائقي وزيادة مساحته في الخارطة البرامجية للقنوات السودانية                 Abstract:      The main objective of this study is to identify the writing requirements for the images in TV documentaries, as well figure out the rules of script writing for documentary and the experience of producing the documentaries in the Sudanese satellite channels. A simple random sample of (11) episodes was selected from 75 episodes of the Sudanese TV documentary "Zool Sudani" that were produced between 2016 -2019. The author used descriptive and inferential statistics for the analysis of the sample data. One of the main obtained results that the direct reporting method used in "Zool Sudani" is the main cause of the production weakness. In this method, the producers explain what the image shows without analyzing and interpreting the displayed image. Interpretation of images lead the viewers to a more convincing and believable vision, and then encourage the imitation of the ideas and adoption of the line of success of the presented character. In addition, the adoption of the principle of (5 seconds or less) in switching between footage without repeating (unless necessary), raises the value of the presented work and keeps it away from traditional and boredomness. The author recommended the motivation of civil society organizations to produce and sponsor documentary programs that aim to consolidate a positive mental image of the Sudanese personality and Sudan as a whole. This production/sponsoring should guarantee the availability of evidence, multiplicity of stories and experiences, raising the level of interest in the documentary artistic product and increasing its time in the Sudanese TV channels.